AKUMULASI LOGAM TIMBAL (Pb) DALAM IKAN BELANAK (Liza melinoptera) YANG HIDUP DI PERAIRAN MUARA POBOYA (Accumulation of Lead (Pb) Metal in Mullets (Liza melinoptera) that Live in Poboya River Estuary) - Melisa Arsad; Irwan Said; Suherman Suherman (Universitas Tadulako, 2013)
Poboya River estuary that known to have been contaminated with heavy metals, one of them is metal lead (Pb). This is because the high human activity in the surrounding waters hed, which may be the source of the entry of heavy metals into the estuary waters. Poboya River estuary has many kinds of marine life, including fish such as Belanak (Liza Melinoptera). Fish used as an indicator of contamination that occurred in the waters. This study aims to determine how much accumulation and metal concentrations of lead (Pb), which accumulates in fish living Belanak Poboya estuaries. The method used is the gravimetric method for determining water content, biomass and low ash content, while the analysis of the samples in this study using Atomic Absorption Spectrometry instrument (SSA). The results showed that the water content mobtained at 55.830%. While the levels of biomass were obtained for 89.200% and ash content of meat samples obtained at 10.790%. While the results showed that the accumulation of the metal lead (Pb) in Belanak fish average of 1.746 ± 1.673mg/kg. That exceeds the maximum value of the metal Lead in food in accordance with ISO 01-2729.1-2006, ie 0.4 mg/kg.